Critical representations of Southern African inequality: Transcending outmoded exhibition and museum politics. Issue 6 (2nd November 2019) - Chipangura, Njabulo; Bond, Patrick; Sack, Steven
ABSTRACT: Illustrating inequality to a more general public – beyond those concerned purely with public policy and research – presents various challenges. Museums have often served a function of memorialising both the impressive steps forward and major barriers to social progress, as a form of remembrance and understanding, although the twentieth century format in South Africa was generally embedded within colonial and racist self-glorification. The potential to transcend outmoded exhibition and museum politics with a new approach based on dialogical not didactic presentation, arises with inequality. In this exploration of how such an approach might unfold in the world's most unequal major city (as judged by the Palma Ratio), Johannesburg, the concept of threshold is introduced. Physical and conceptual access through overcoming thresholds is explored through a specific site, the Old Post Office, and through two artifacts that reveal structural power that generates inequality: Durban's sanitation system and Eastern Zimbabwe's diamond fields.